The Relationship Between Interpersonal Communication And Social Intelligence In Online Learning On Social Knowledge Learning Outcomes (Ips) Elementary School Students - Lestari, Nur'im Septi; Lestari, Nining Puji (Jurnal Ilmiah Mandala Education (JIME), 2023)
There are no packages and require more costs in the learning process. Researchers are interested in researching the relationship between Interpersonal Communication and Social Intelligence in Online Learning on Social Science Learning Outcomes (Ips) of Bancar Elementary School Students. The research method that researchers use is quantitative. Collecting data using interviews, observation and distribution of questionnaires to fifth grade students. The results of this study are based on the attached tcount value of 8.814 and a significance of 0.000. Because tcount > ttable (8.814>2.048) or significance <0.05 (0.000<0.05) then Ha is accepted and ho is rejected meaning that there is a significant relationship between interpersonal communication in online learning and student learning outcomes in social studies subjects at Bancar. In the attachment the tcount value is 0.323 and a significance of 0.750. Because tcount < ttable (0.323>2.048) or significance <0.05 (0.750>0.05) then Ho is rejected and ha is accepted meaning that there is no significant relationship between social intelligence in online learning and student learning outcomes in social studies subjects at Bancar.